A Comparative Study of DC and BLDC Actuation for Kinesthetic Haptics - Arjun Ivimey; Majid Pahlevani; Keyvan Hashtrudi-Zaad (IEEE Access)
Haptic simulation systems enable users to manipulate virtual environments through their interaction with haptic devices. Stable high fidelity interaction with virtual environments for many applications requires actuators with both high torque density and low parasitic forces. Brushless direct-current (BLDC) motors offer both high torque density and low friction, making them a prime candidate for this application. This paper evaluates the use of a BLDC motor for use as a direct drive haptic actuator, in comparison with the brushed direct-current (DC) motor and capstan mechanism commonly used in indirect drive actuation of haptic devices. The comparison metrics include data sheet parameters, peak torque determined using a thermal simulation, current and position step responses, uncoupled stability regions, and dynamic rendering areas. It is concluded that a direct drive BLDC motor can supply higher peak torque, while projecting lower inertia and friction and thus offering higher acceleration. These results indicate that BLDC motors are a promising technology for effective direct drive haptic actuation.